ANALISIS DAMPAK RAMADHAN TERHADAP KINERJA IHSG DAN INDEKS SEKTORAL PERIODE 2008 – 2018 - Anggi Puspa Pradhini; Fadlul Imansyah (Jurnal Ekonomi dan Bisnis, 2019)
This research aims to analyze trend of stock volatility during Ramadhan, both on the compositeindex (IHSG) and sectoral price index. This research employs data ranging from 2008 – 2018accessed from Eikon – Centre of Economic and Business Data Faculty of Economics andBusiness Universitas Indonesia. In order to analyze whether or not price volatility might differbetween Ramadhan and other periods, this research employs Non-Parametric Mann WhitneyTest, where the result shows that there is not significant difference of stock price volatilitybetween Ramadhan and other periods, as shown by p-values above error level by 5%. DuringRamadhan, the increase in stock price is not as high as those in other periods, even at thesame time, trade during Ramadhan tends to be more dynamic (higher variance). In order toanalyze trend of stock price during Ramadhan, this research employs ARCH GARCH Model,where healthcare sector is the only that experience significant increase in stock price duringRamadhan along 2008 – 2018. The ARCH coefficient is 0.996, while the GARCH coefficientis 0.128. If analyzed deeper, IHSG return during Ramadhan is not significantly different fromother months along 2008 – 2018, even lower. During Ramadhan, the average growth of IHSGreturn is -0.04%, while during other periods, the average growth is 0.07%. Nevertheless, theresult appears to be different when analyzed using sectoral industry return. According to dataprocessing of the research, it is found that healthcare sector is the only one that is increasingduring Ramadhan. Along 2008 – 2018, the increase in return of healthcare sector is 3.21%,while in other periods, it is only increasing by 0.41%. The increase in return of healthcaresector has been mainly driven by the increase in positive expectation of investor due to highersales performance of firms in healthcare industry. The main sales increase focuses on nutritionproduct and prescription medication. Therefore, this finding can be a strategic consideration forinvestor to gain more return upon their portfolio investment.Keywords: Pasar Modal, IHSG, Saham Sektoral, ARCH GARCHJEL Classifications : G1 G110 C580 G120